.66x+8-1=1.33x-3+x

Simple and best practice solution for .66x+8-1=1.33x-3+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for .66x+8-1=1.33x-3+x equation:


Simplifying
0.66x + 8 + -1 = 1.33x + -3 + x

Reorder the terms:
8 + -1 + 0.66x = 1.33x + -3 + x

Combine like terms: 8 + -1 = 7
7 + 0.66x = 1.33x + -3 + x

Reorder the terms:
7 + 0.66x = -3 + 1.33x + x

Combine like terms: 1.33x + x = 2.33x
7 + 0.66x = -3 + 2.33x

Solving
7 + 0.66x = -3 + 2.33x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2.33x' to each side of the equation.
7 + 0.66x + -2.33x = -3 + 2.33x + -2.33x

Combine like terms: 0.66x + -2.33x = -1.67x
7 + -1.67x = -3 + 2.33x + -2.33x

Combine like terms: 2.33x + -2.33x = 0.00
7 + -1.67x = -3 + 0.00
7 + -1.67x = -3

Add '-7' to each side of the equation.
7 + -7 + -1.67x = -3 + -7

Combine like terms: 7 + -7 = 0
0 + -1.67x = -3 + -7
-1.67x = -3 + -7

Combine like terms: -3 + -7 = -10
-1.67x = -10

Divide each side by '-1.67'.
x = 5.988023952

Simplifying
x = 5.988023952

See similar equations:

| 2(w+9)=4w+26 | | (x-3)2+(y+5)2=64 | | 5+0.142857143x=7 | | x+6=8+x-2 | | 0=14x^2-11+2 | | 3v-22=-2(v+1) | | 14+y=20-14 | | 3.6x=14.4 | | 11x-5=8x+8 | | 0.3x+0.25=0.4-0.6x+0.4 | | y+4.5=10 | | 4x-3=6+5x | | 15y=2-4 | | -5x-2=5x+28 | | 10+11x=-14 | | 12-3d=-3 | | 9+6x=3x-15 | | onehalfx+3=7 | | -5x+8=-7x-16 | | 4.5=34.5-3w | | 4ln(6y-1)=36 | | x-5-10=15 | | 0.72x+0.5=0.3-0.27x+0.3 | | -5x+1=2-6x | | x+4=7.5 | | -5x+1=5x-9 | | -X+8.5=14.2 | | 3x-9=-73-5x | | forx=7 | | 8+4x=-4x+80 | | 8x+16=23 | | 4(x+1)+3x+7=52 |

Equations solver categories